GEOMETRY OF SORBED ARSENATE ON FERRIHYDRITE AND CRYSTALLINE FEOOH: RE-EVALUATION OF EXAFS RESULTS AND TOPOLOGICAL FACTORS IN PREDICTING SORBATE GEOMETRY, AND EVIDENCE FOR MONODENTATE COMPLEXES - Waychunas G.A.; Davis J.A.; Fuller C.C. (My University, 1995)
Manceau's (1995) reinterpretation of some of our EXAFS results (Waychunas et al., 1993) has been analyzed using both old and newly collected data in an attempt to clarify the nature of proposed monodentate and edge-sharing bidentate arsenate complexes on the ferrihydrite surface. It is shown that EXAFS analysis utilizing data with sufficient k-range does indicate the presence of relatively short As-Fe bonds, suggestive of an edge-sharing complex as indicated by Manceau (1995). However, a variety of data analysis factors and crystal chemical considerations create doubt in this assignment. Most significantly, X-ray scattering data collected on a sample of ferrihydrite with a large density of sorbed arsenate, which should show a substantial fraction of the edge-sharing complex, does not show any such correlation within fitting uncertainty. We also suggest that it is unnecessary to invoke the presence of edge-sharing bidentate arsenate to explain the surface growth poisoning of ferrihydrite with increasing sorbed arsenate, as Manceau (1995) claims. Further, we show that a model based on the topology of close packed oxygen ions offers a clear explanation why monodentate arsenate should appear on some surfaces and not on others, and why differing As-Fe distances might be observed on a single surface with a single type of complex. This model also explains why bidentate sorbed arsenate can occupy positions with consistent ?tilt? angles. Without such consistency, the sorbed arsenate would be highly positionally disordered, and difficult to detect accurately via EXAFS methods.